SISTEMA ÚNICO DE SAÚDE: DO PROTAGONISMO AOS DESAFIOS ATUAIS - Daniel de Macedo Rocha; Ítalo Arão Pereira Ribeiro; Ingrid Moura de Abreu; Iara Barbosa Ramos (Sociedade Brasileira de Enfermagem em Feridas e Estética, 2024)
Editorial